Políticas públicas em educação e prevenção contra incêndio e pânico: formulação de mecanismos de avaliação e controle - Schunig, Fernando Raimundo (2015)
The fires have always been a concern for the Fire Department, however, fires still going on, people lose their lives and property are destroyed. So that there is a change in this scenario is necessary to implement Public Policies in Education and Fire Prevention and panic, as well as setting numerical indices that serve as parameter for the establishment, development and evaluation of these policies. Once defined an index, it will be possible to evaluate the safety of the building due to the preventive measures and potential hazards, determination of mitigating actions the risk of fire and its use for the development of actions aimed at education on fire prevention. The objective of this research is to study the feasibility of using the evaluation index of fire risk obtained by Gretener method, adapted to serve as a numerical indicator for the establishment, development and evaluation of public policies in education and fire prevention and panic. For this survey, a comprehensive theoretical study on the subject was made to trace current expectations of Fire Prevention Panic and also carried out a field survey that realized own survey of the application, with the public researched firefighters, engineers and architects working in the analysis and preparation of Safety Plans Fire and Panic in Cascavel. As a result, it was evident that the risk assessment index fires Gretener method, adapted to the current legislation in the State of Paraná can be used widely for the formulation and evaluation of public policies in education and fire prevention and panic because it meets all conceptual and methodological requirements, and may be a useful mechanism for planning, representing a great potential for public policy establishment.